Surgical technique of tunneling for gingival recession recovery – clinical case report (Research, Society and Development, 2021)
Connective tissue graft associated with surgical tunneling technique has been cited as favorable option for the treatment of moderate. Miller class I and II gingival recession. This presente article aims to report a clinical case of a 43-yers-old male patient selected for the treatmente of gingival recession of tooth 41. After clinical and radiographic evaluation, we concluded that it was a Miller class I recession. It was decided to proceed surgically with the root coverage of this tooth using the tunneling technique. One month after the procedure, complete root coverage, no bleeding on probing depth of 3 mm and perfectesthetic integration with the with the adjacente tissues were observed. In view of the aforementioned case, it is clear that this technique presentes very predictable results When indicated and executed correctly, thus reaching a very aesthetic result.